Does formal strategic planning matter? An analysis of strategic management and perceived usefulness in Norwegian municipalities. (June 2021) - Johnsen, Åge
This article assesses whether municipal managers perceive strategic planning as most useful when integrated into mandatory area or financial-planning processes or conducted in processes with separate strategic planning documents. Despite being widely adopted in practice and being extensively debated in scholarly discourse for decades, current research has little empirical grounding for providing advice for policymakers and public managers on such common design choices. Multiple regression analysis of 128 Norwegian municipalities shows that using a voluntary separate strategic planning document was related to top management's perceived usefulness of strategic planning. Integrating strategic planning into other management processes was also related to the perceived usefulness of strategic planning. Unexpectedly, using mandatory planning documents (such as four-year financial plans and long-term area plans) as the main strategic planning documents, formality and stakeholder involvement in the planning processes were not related to the perceived usefulness of strategic planning. Points for practitioners: Planning, and in particular formal strategic planning, is often criticized both by scholars and practitioners as being useless when the environments are uncertain and turbulent, and for draining the organizations' resources from other important management tasks. This article shows that many municipalities voluntarily produced separate strategic planning documents and that municipal top management found these plans more useful than using mandatory financial plans or area plans as their main strategic planning documents.